(untitled) (Bisanzio e l’Occidente, 2019)
The paper deals with Euripides’ Andromache — verses and scholia — in the Ilias Picta Ambrosiana, focusing on their text and on the signification of the Euripidean presence both on the late-antique miniatures and in the twelfth-century manuscript on which the miniatures had been placed, containing Homeric scholia.